Peran WisataIdalam Meningkatkan Perekonomian dan UMKMIMasyarakat Idi Desa Sopotinjak Mandailing Natal - Aldi Fernando; Tri Inda Fadhila Rahma; Wahyu Syarvina (VISA: Journal of Vision and Ideas, 2023)
At present the tourism sector is one of the very promising industries, in order to improve the economy of the people in tourism objects not only for share owners, but in fact the existence of tourism objects also has a role in the economy of the surrounding community. The aim of this research is to find out how the impact of tourism on improving the economy of the community on the idea of ​​IUMKM and to find out the impact of tourism on improving the IUMKM on the community on the idea of ​​Sopotinjak. The method of this research uses a descriptive-qualitative method. The result of this research is that the tourism sector is one of the people's economic potentials that needs to be developed in order to increase people's welfare. The existing tourism potentials have not yet been fully developed, even though these potentials are very promising. The funds for the establishment of the immanent ones come from self-help in the community. The interest of investors in investing in the activities of establishing the Desa Tourism Sopotinjak is still very minimal. So that infrastructure and infrastructure in there have not yet been fully fulfilled i.e. with the existence of tourism objects in an area i will directly open up jobs and fields for the surrounding community especially in the surrounding area i. is one of the tourism objects that becomes the object of research. Keywords: Society's Economy, Economy Industry, Tourism's Role, UMKM